Plan de negocio para la creación de una empresa de producción y comercialización de muebles de madera vintage, cantón Buena Fe, año 2014 - Herrera Guerrero, Maritza Fabiola (2014)
Actually in the market of Buena Fe existence various locals where himself commerce movable and inexistent of companies producing furniture. The business plan for the creation of a marketing company and furniture production was carried out during 2013-2014, information was obtained through surveys of 379 habitants and interviews applied to the proprietarys of the furniture stores them encounter in the land census municipal. Taking in count these points are intended to solve an existing need for developing a business plan for the creation of a production and marketing of vintage wooden furniture. Canton Buena Fe 2014, and thus meet the unmet demand of consumers, furniture company focuses on marketing and producing wooden furniture vintage furniture from the latest being to create quality furniture to your taste and choice. The company will be called " Josenk " , its location will be on August 7th Avenue Santo diagonal path to the restaurant Sunflowers Monday. Advertising is the conduct by (flyers leaves) and radio (stereo Good Faith). For the implementation of the business invested $ 47,517, 10 is required with a 5 % contingency it will be financed by 74 % for a credit than it held in the National Corporación Finaniera (CFN) , with interest 11.83 % 3 year term , and he 26% by the investment a observativa research and interviews to competition in order to obtain information to calculate the sales that have the furniture " Josenk " was made. The analysis and financial evaluation determines that it is feasible because the NPV indicators equals $ 135,262.26, with positive values indicating that the business plan is viable. TIR is equal to 86 %, with a greater rate than is used for calculations. This indicates that the business plan is profitable for investors. RB / C is equal to 1.40 obviously is greater than 1, indicating that the business plan is profitable. The plan is projected to 5 years but the payback will be in one year with 100 days.